Tunable Organic Hetero‐Patterns via Molecule Diffusion Control. Issue 15 (14th April 2014) - Wang, Hong; Wang, Wenchong; Li, Liqiang; Hirtz, Michael; Wang, C. G.; Wang, Yue; Xie, Zhaoxiong; Fuchs, Harald; Chi, Lifeng
<x xml:space="preserve">Abstract</x> A simple, scalable method is reported to fabricate ordered hetero‐structures of organic materials using template‐directed growth. The 3D extension of the structures is firstly determined by pre‐pattern size and deposition amount, and can further be in situ tuned by annealing at appropriate temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>